DIALOG RESEPSI JAMĀ’AH TABLĪGH TERHADAP QS. ALĪ-IMRĀN [3]: 104 DENGAN DAN QS. AL-AHZĀB [33]: 33 TENTANG PERAN PEREMPUAN DALAM DAKWAH - Aisyah; Muh. Ikhsan (EL-MAQRA', 2025)
This study examines the reception dialogue of Jamā'ah Tablīgh regarding QS. Āli-'Imrān :104 concerning the obligation to preach and QS. al-Ahzāb :33 regarding women's roles at home. Using a qualitative approach with the Living Qur'an method, this research was conducted from February to May 2024 at Al-Markaz Jamā'ah Tablīgh, Bombana District, Southeast Sulawesi. Data were collected through in-depth interviews with 8 informants (5 women, 3 men), participatory observation, and document study, then analyzed using the Miles & Huberman model. The findings reveal that Jamā'ah Tablīgh does not experience contradiction in understanding the two verses. QS. Āli-'Imrān :104 is understood as a universal preaching obligation for all Muslims including women, in line with contemporary tafsir. QS. al-Ahzāb :33 is interpreted not as an absolute prohibition but as guidance to prioritize household as the primary center of activity while still allowing women to go out for religious necessity. Jamā'ah Tablīgh integrates the two verses through developing special preaching programs for women (ta'lim, halaqah, bayan, ijtima') that enable women to develop spiritually and intellectually without compromising family commitment. These findings demonstrate that Muslim communities are capable of performing intelligent hermeneutical contextualization in receiving the Qur'an, integrating traditional values with modern contextual needs. This research contributes to Living Qur'an studies by demonstrating how the Qur'an "lives" through complex hermeneutical processes and the development of social programs based on community theological understanding.